An analysis of the relationship between the sources of conflict and the stages in the conflict process within the marketing channel comprising retail pharmacy managers and medical doctors - Futter, William Thomas (Rhodes University, Faculty of Commerce, Department of Management, 1988)
Marketing channels have traditionally been examined as commercial conduits the sale objective of which was to facilitate the flow of goods from producer to consumer. This approach emphasized functional and structural aspects of the channel and was primarily concerned with the efficiency of the distribution system. During the last two decades, marketing channels have increasingly been viewed as social systems affected by the behavioural dimensions of power, conflict, roles and communication. The rapid growth of vertical marketing systems with greater authority and interdependence between channel members, have stimulated interest in this field. Nevertheless, research has been limited and characterized by methodological problems and conceptual differences about the definitions of behavioural variables and their relationships. Some attempts have been made to develop an integrated framework within which to conduct research into channel relationships, but the validity and relaibility of these models has not been tested. This research project examined the relationship between the sources of conflict and stages in the conflict process. The sources of conflict were subdivided into attitudinal and structural categories, the latter being concerned with goal differences, the desire for autonomy in the face of interdependence and competition for scarce resources. The conflict process model adopted by the author assumes the existence of stages of latency, feeling, perception, manifestation and aftermath in each conflict episode. The first four were treated as separate behavioural states for which different levels of conflict intensity were measured. In order to provide greater explanatory power to the results of the analysis, the perceptions of two respondent groups were identified, namely the leader group, consisting of channel members responsible for the overall strategic interests of the channel, and the affected group, consisting of channel members who had been adversly affected by the activities of their partners in the channel dyad. In addition, respondents were asked to identify separately, their perceptions of the macro and micro levels of conflict in the four conflict states. The marketing channel for prescription medicines was selected for the study. The focal dyad consisted of retail pharmacy managers and doctors with single respondent perceptual measures being obtained from the retail pharmacy managers. A mail survey of all the retail pharmacy managers in South Africa, South West Africa/Namibia, and the independent homelands conducted in July 1987 resulted in a 40% response rate (1031 returns). Tests indicated statistically significant differences between the perceptual measures representing the sources and stages of conflict, the macro and micro levels of the stages of conflict and between the leader and the non-leader groups and the affected and non-affected groups. A sequential hierarchy in the level of conflict measured in the behavioural states was indicated, with decreasing levels of conflict being identified in states of latency, perception, feeling and manifestations, respectively. An analysis of the results revealed that attitudinal sources of conflict were more important that structural sources in measures of perceptions, feelings and manifestations of conflict behaviour. In the latent conflict state, structural sources assumed greater importance than attitudinal sources. In most of the measures, the sources of conflict were more correlated with perceptions of conflict at the macro level than the micro level. The exception was manifest conflict for which micro conflict levels were more important. The major sources of conflict were differences in perceptions, differences in goals and the lack of autonomy. The leader group indicated a particular concern for attitudinal factors, particularly communication difficulties. The affected group, whilst identifying attitudinal factors as being the most important, was especially concerned with their lack of autonomy from the doctor, rather than the competition for scarce resources which could have been expected. An overall assessment of the level of conflict between retail pharmacy managers and doctors indicated that the channel dyad was relatively free from conflict. Relationships were characterized by a degree of satisfaction, some degree of harmony and little evidence of conflict behaviour.
Keywords: Medicine -- Formulae, receipts, prescriptions -- Marketing; Marketing channels; Marketing research; Drugs -- Marketing